EFFECT OF FLUNIXIN MEGLUMINE ON CONCEPTION RATE FOLLOWING EMBRYO TRANSFER IN CROSSBRED CATTLE - MALIK, ANKIT; PRASAD, SHIV; KUMAR, SUNIL; MATHANI, MAYANK; GUPTA, H P (The Indian Journal of Animal Reproduction, 2022)
The present study was designed to study the effect of flunixin meglumine following embryo transfer during luteal phase of estrous cycle on Prostaglandin fetal metabolite (PGFM) and progesterone in embryo recipient cows. Eighteen crossbred cows were selected and divided into three groups; Control (n=6): NSS, T-I (n=6): flunixin meglumine @ dose rate of 1.1 mg/kg half-hour before transfer, T-II (n=6): flunixin meglumine @ dose rate of 1.1 mg/kg half-hour before transfer and on Day 16 and Day 17 of oestrous cycle. Blood samples were collected on 7½ day of oestrous cycle without any treatment i.e. before embryo transfer and then half an hour after treatment. Again blood samples were taken at 15 minute, 50 minute and 150 minute following embryo transfer, On day 16, 17 and 18 of estrous cycle, blood sampling was done every 12 hour and for progesterone estimation blood samples were taken before treatment/ transfer, 150 min after transfer/treatment then on 16th , 17th , 18th , and 32nd day following estrus. Results of the study showed that the PGFM level and progesterone level differ non-significantly (p>0.05) between the groups but after treatment, there was marked decrease in PGFM level and simultaneously increased progesterone concentration. Out of three pregnancies, one animal aborted on day 76 of gestation. On the basis of above findings, it may be concluded that administration of flunixin meglumine during luteal phase of estrous cycle may be beneficial in improving the conception following embryo transfer in crossbred cattle as evident by decreased level of PGFM and increased level of progesterone during critical days of maternal recognition of pregnancy.